2009
DOI: 10.1128/jvi.01263-08
|View full text |Cite
|
Sign up to set email alerts
|

Pre-P Is a Secreted Glycoprotein Encoded as an N-Terminal Extension of the Duck Hepatitis B Virus Polymerase Gene

Abstract: The duck hepatitis B virus (DHBV) pregenomic RNA is a bicistronic mRNA encoding the core and polymerase proteins. Thirteen AUGs (C2 to C14) and 10 stop codons (S1 to S10) are located between the C1 AUG for the core protein and the P1 AUG that initiates polymerase translation. We previously found that the translation of the DHBV polymerase is initiated by ribosomal shunting. Here, we assessed the biosynthetic events after shunting. Translation of the polymerase open reading frame was found to initiate at the C1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Translation of the polymerase ORF was also found to initiate at two upstream in-frame AUGs, C13 and C14, in addition to the P1 AUG, and we confirmed that initiation at the C13 AUG occurs through ribosomal shunting (2). C13 and C14 are in frame with P1, and initiation at these start codons leads to production of glycosylated isoforms of P called "pre-P" in the majority of DHBV strains because most DHBV isolates lack the S10 stop codon found downstream of the C14 AUG in DHBV strain 3 (2). In this study, we extended these observations by mapping the shunt donor and acceptor sequences as a prelude to examining the DHBV shunting mechanism.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…Translation of the polymerase ORF was also found to initiate at two upstream in-frame AUGs, C13 and C14, in addition to the P1 AUG, and we confirmed that initiation at the C13 AUG occurs through ribosomal shunting (2). C13 and C14 are in frame with P1, and initiation at these start codons leads to production of glycosylated isoforms of P called "pre-P" in the majority of DHBV strains because most DHBV isolates lack the S10 stop codon found downstream of the C14 AUG in DHBV strain 3 (2). In this study, we extended these observations by mapping the shunt donor and acceptor sequences as a prelude to examining the DHBV shunting mechanism.…”
supporting
confidence: 75%
“…We previously found that translation of the DHBV P ORF initiates at the upstream in-frame C13 and C14 AUGs, in addition to the P1 AUG, and initiation at C13 was demonstrated to occur by ribosomal shunting (2). Translation from the C13 AUG in the absence of the S10 stop codon produces a glycosylated P isoform called pre-P in which the leader sequences appear to be removed following translocation into the endoplasmic reticulum (2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation